Solar energy as an alternative option in cathodic protection system for sustainable structure - 325936 Muhamad Abid Abdullah (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006